Pengaruh Gaya Hidup (Lifestyle), Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Di Masa Pandemi Covid-19 (Studi Kasus Pada Konsumen Dunia Cell, Pare-Kediri) - Umi Khoirun Nisa’; Siti Kalimah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The purchase decision is an act of consumers to choose the preferred product with a variety of existing choices or in the presence of other alternatives. In this thesis entitled "The Influence of Lifestyle, price and product quality on smartphone purchasing decisions during the COVID-19 pandemic (Case Study in Pare-Kediri Cell World)". The purpose of this study was to analyze the effect of lifestyle, price and product quality on smartphone purchasing decisions during the COVID-19 pandemic. This research is a quantitative research, with data collection techniques in this study using questionnaires and interviews. The sampling technique used is probability sampling technique with random sampling method. then obtained a sample of 96 respondents. The analysis technique used is multiple linear regression analysis and partial and simultaneous hypothesis testing. The results of this study indicate that the variables of lifestyle, price and product quality have a partial influence on smartphone purchasing decisions. It is proven by the lifestyle variable that has a sig value. < 0.05 and tcount 5.055 > 1.9860 ttable, the price has a value of tcount 4.668 > 1.9860 ttable, and the value of product quality is tcount 2.201 > 1.9860 ttable. With the results of the simultaneous test (F) on the three variables, together have a significant effect on purchasing decisions with a sig value. 0.000 < 0.05 and tcount 236, 705 > 2, 703 t table. With an R Square value of 0.885 or 88, 5%.